2022
DOI: 10.1021/acsami.1c23176
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable, Adhesive, Self-Healable, and Conductive Hydrogel-Based Deformable Triboelectric Nanogenerator for Energy Harvesting and Human Motion Sensing

Abstract: Hydrogels that combine the integrated attributes of being adhesive, self-healable, deformable, and conductive show great promise for next-generation soft robotic/energy/electronic applications. Herein, we reported a dual-network polyacrylamide (PAAM)/poly­(acrylic acid) (PAA)/graphene (GR)/poly­(3,4-ethylenedioxythiophene):poly­(styrene sulfonate) (PEDOT:PSS) (MAGP) conductive hydrogel composed of dual-cross-linked PAAM and PAA as well as PEDOT:PSS and GR as a conducting component that combines these features.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(73 citation statements)
references
References 59 publications
0
73
0
Order By: Relevance
“…It can be concluded that the sensitivity of both the voltage and resistance responses of the Pp-250 improved after mixing the two fillers. Compared with other research results, ,,,,, the Pp-250 prepared by us has more advantages in response time and recovery time indexes and can achieve a fast and sensitive response (Figure g).…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…It can be concluded that the sensitivity of both the voltage and resistance responses of the Pp-250 improved after mixing the two fillers. Compared with other research results, ,,,,, the Pp-250 prepared by us has more advantages in response time and recovery time indexes and can achieve a fast and sensitive response (Figure g).…”
Section: Resultsmentioning
confidence: 64%
“…Hydrogels are flexible materials with three-dimensional cross-linked hydrophilic polymer networks. Conductive hydrogels combine the electrical properties of conductive materials with the flexibility and biocompatibility of hydrogels and have been widely used in flexible sensors, wearable electronic devices, electronic skin, and other fields. In recent years, wearable sensors based on conductive hydrogels have attracted much attention.…”
Section: Introductionmentioning
confidence: 99%
“…2 b). Wang et al [ 28 ] used polyacrylamide/polyacrylic acid/graphene/poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) hydrogel incorporated with CNTs and polydimethylsiloxane (PDMS) to fabricate TENG, which can be used to monitor human activities and harvest energy from human motion. Piezoelectric sensors mostly require inorganic materials to synthesize piezoelectric composites to improve their performance, which is still a major challenge.…”
Section: Physical Sensormentioning
confidence: 99%
“…Flexible electronic devices such as wearable sensors, nanogenerators, , and flexible batteries , have attracted social-level attention, because of their portability and wide range of applications. Various strain and pressure-based wearable sensors have been fabricated to fulfill the requirements of diverse application scenarios. , Notably, hydrogel-based flexible electronics have been widely studied, because of their versatility, mechanical compliance, and good biocompatibility .…”
Section: Introductionmentioning
confidence: 99%